2009
DOI: 10.2478/v10120-009-0001-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liquid pig manure fertilization on the density and species structure of Oribatida (Acari) and green forage yield in a lowland meadow in Poland

Abstract: Effects of liquid pig manure fertilization on the density and species structure of Oribatida (Acari) and green forage yield in a lowland meadow in PolandThe effect of liquid pig manure fertilization, with or without the disinfectant VIT-TRA, on oribatid communities was investigated in a lowland meadow in Poland. The disinfectant was tested at 3 concentrations: 0.50% (fungicidal), 0.75% (bactericidal), and 3.00% (viricidal). Liquid pig manure without the disinfectant increased the green forage yield along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…A higher dose of the fertilizer with viricide increased the density of L. humerata, P. bella and S. laevigatus in the summer, compared to the control plot. seniczaK et al (2006) observed an increasing density of Liebstadia similis (Michael, 1888) and S. laevigatus in the summer, after using a high dose of ammonia water, whereas WasińsKa-graczyK et al (2009) noted the increased density of oribatid mites under a high dose of pig liquid manure and viricide.…”
Section: Resultsmentioning
confidence: 99%
“…A higher dose of the fertilizer with viricide increased the density of L. humerata, P. bella and S. laevigatus in the summer, compared to the control plot. seniczaK et al (2006) observed an increasing density of Liebstadia similis (Michael, 1888) and S. laevigatus in the summer, after using a high dose of ammonia water, whereas WasińsKa-graczyK et al (2009) noted the increased density of oribatid mites under a high dose of pig liquid manure and viricide.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Bielska (1986) observed a decrease in the density and number of species of Oribatida with an increasing amount of liquid manure. In other studies, however, high doses of liquid manure in the grasslands reduced the density of the mites, but not their species richness (Bolger & curry 1980;Domek-chruścicka & Seniczak 2005;SokołowSka & Seniczak 2005;graczyk et al 2008;waSińSka-Graczyk et al 2009;kruczyńSka & Seniczak 2011).…”
Section: Discussionmentioning
confidence: 90%
“…So far the studies on the effects of organic fertilizers on oribatid mites of meadows focused on liquid manure, produced mostly by cattle (Bielska 1986;SokołowSka & seniczak 2005;graczyk et al 2008, 2010kruczyńSka & Seniczak 2011) and sometimes by pigs (Domek-chruścicka & Seniczak 2005;waSińSka-Graczyk et al 2009). nakaMura (1976) studied in a pasture the effect of cattle manure on the soil microarthropods, including the Acari and the Oribatida, but all the Oribatida were considered jointly, so we do not know about the reaction of different species to manure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most ecological studies (mainly in Poland) on mites in grasslands focused on the effect of fertilizers or ecotones (Domek-Chruścicka and Seniczak, 2005;Graczyk et al, 2008Graczyk et al, , 2010Kruczyńska and Seniczak, 2010;Seniczak et al, 2016;Wasińska-Graczyk et al, 2009), while relatively few papers analyzed the direct impact of grazing on mite communities (Hubert, 2000;Chachaj and Seniczak, 2006;Seniczak et al, 2007;Schon et al, 2008Schon et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%